Clinical Manifestation and Hematologic Interpretation of Pediatric Systematic Lupus Erythematosus at Initial Presentation: 2-Years Observation - Hasti Savira Yudiana; Reni Ghrahani; Adhi Kristianto Sugianli (Faculty of Medicine Universitas Padjadjaran, 2021)
Background: Systemic Lupus Erythematosus (SLE) is an autoimmune disease characterized by a spectrum of clinical manifestations, immunological abnormalities, and varied laboratories results. In children, SLE manifestation is particularly more severe, involving more organs. Hematological manifestation has been known as the most common manifestation. The purpose of this study was to describe the clinical manifestations and hematologic interpretation of pediatric SLE at initial presentation.Methods: This retrospective data collection study was conducted at the Department of Child Health Dr. Hasan Sadikin General Hospital Bandung on medical records from a two-year period of 2017–2018. The clinical manifestations were categorized into malar rash, discoid rash, photosensitivity, oral ulcers, arthritis, renal disorders, and neurological disorders. The hematologic interpretations were categorized into anemia, leukopenia, neutropenia, lymphopenia, and thrombocytopenia. Clinical manifestations and hematological interpretations were presented as occurrence percentages and stratified into three age-group of pre-pubertal, peri-pubertal, and post-pubertal.Results: Among 79 pediatric SLE patients (median age 14 years old; IQR 11–16), female gender was predominant. Abnormalities hematologic interpretation occurs in more than half of the patients (83.5%). Malar rash and anemia were the commonest findings among all age groups. Increased occurrence of neuropsychiatric and renal disorders were observed in all age-groups.Conclusions: Malar rash and anemia are important findings among pediatric SLE patients. Furthermore, the occurrences of the neuropsychiatric and renal disorders are also important.